Learning in lockdown: Using the COVID‐19 crisis to teach children about food and climate change. Issue 2 (26th February 2021) - Kluczkovski, A.; Lait, R.; Martins, C. A.; Reynolds, C.; Smith, P.; Woffenden, Z.; Lynch, J.; Frankowska, A.; Harris, F.; Johnson, D.; Halford, J. C. G.; Cook, J.; et al.
Abstract: Food systems are significant sources of global greenhouse gas emissions (GHGE). Since emission intensity varies greatly between different foods, changing food choices towards those with lower GHGE could make an important contribution to mitigating climate change. Public engagement events offer an opportunity to communicate these multifaceted issues and raise awareness about the climate change impact of food choices. An interdisciplinary team of researchers was preparing food and climate change educational activities for summer 2020. However, the COVID‐19 pandemic and lockdown disrupted these plans. In this paper, we report on shifting these events online over the month of June 2020. We discuss what we did and the reception to our online programme. We then reflect on and highlight issues that arose. These relate to: (1) the power dynamics of children, diet and climate change; (2) mental health, diet and COVID‐19; (3) engaging the wider science, agriculture and food communities; (4) the benefits of being unfunded and the homemade nature of this programme; (5) the food system, STEAM (science, technology, engineering, arts and mathematics) and diversity; and (6) how our work fits into our ongoing journey of food and climate change education.